Thyroid Hormone and Blood Metabolites Concentration of Gilts Superovulated Prior to Mating - Mege, RA; Manalu, W; Kusumorini, N; Nasution, SH (ANIMAL PRODUCTION, 2009)
An experiment was conducted to study injection of pregnant mare serum gonadotrophin (PMSG) and human chorionic gonadotrophin (hCG) as superovulation agent in gilts to improve thyroid hormone and blood metabolites concentraton. In this experiment, 48 gilts were assigned into four groups of twelve gilts injected with PMSG dan hCG dose levels of 0, 600, 1200 and 1800 IU/gilt. Injections were conducted three days before estrus. During  gestation, gilts were placed in colony pigpen. On days 15, 35, and 70 of gestation blood collected to determine triiodothyronine, tetraiodothyronine, tryglicerides, glucose, protein and bood nitrogen urea concentration. The resuts showed that superovulation dose levels of 600 to 1200 IU/gilt increased concentration of thyroid hormone (triiodothyronine and tetraiodothyronine/thyroxin) and blood metabolite (triglycerides, glucose, and protein), but decreased blood urea nitrogen in gestation ages 15, 35, and 70 days.  It is concluded that superovulation with dose of 600 to 1200 IU can improve of gilts metabolite hormone and blood metabolites. (Animal Production 11(2): 88-95 (2009) Key Words:  gilts, superovulation,  metabolite hormone, blood metabolites